2020
DOI: 10.1186/s41983-020-00171-6
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s palsy: clinical and neurophysiologic predictors of recovery

Abstract: Background: The annual incidence of Bell's palsy (BP) is 15 to 20 per 100,000 with 40,000 new cases each year, and the lifetime risk is 1 in 60. For decades, clinicians have searched the prognostic tests of sufficient accuracy for acute facial paralysis. Objective: The present study was designed to verify in BP which clinical or electrophysiological parameters could be considered as predictive of the degree of recovery of normal facial muscle function. Methods: Sixty-three patients with BP were initially asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…On multivariable logistic regression analysis, favorable outcome was observed with female gender, younger age group, lower initial H-B Grade, absence of hypertension and treatment with steroid and antiviral drugs (Table III). 11 showed that age, sex, hypertension, diabetes and dyslipidemia did not correlate with the degree of recovery in BP. In our study, female sex was associated with good prognosis initially but later on in univariate and multivariate regression analysis it was not appear to be significant factor for favorable outcome.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On multivariable logistic regression analysis, favorable outcome was observed with female gender, younger age group, lower initial H-B Grade, absence of hypertension and treatment with steroid and antiviral drugs (Table III). 11 showed that age, sex, hypertension, diabetes and dyslipidemia did not correlate with the degree of recovery in BP. In our study, female sex was associated with good prognosis initially but later on in univariate and multivariate regression analysis it was not appear to be significant factor for favorable outcome.…”
Section: Resultsmentioning
confidence: 96%
“…Generally, the prognosis of BP is good, with 71% patients regain normal function with or without medical therapy, often within 3 weeks and within next 3 to 5 months improves further 10,11 but up to 30% cases are left with potentially disfiguring facial weakness, involuntary movements and/or persistent lacrimation requiring further interventions. [12][13][14] Therefore, the resolution of BP and risk of paralysis are of great concern to patients.…”
Section: Introductionmentioning
confidence: 99%
“…The face becomes asymmetrical and is drawn up to the normal side [14]. The affected side is motionless [15]. Result is asymmetry of corner of mouth, inability to close the eye and disappearance of nasolabial fold [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no known reports of development of Bell's palsy with WNV encephalitis. The annual incidence of Bell's palsy is 40 000 new cases each year with 8% to 12% recurrence rate 13 . Up to 70% of patients will have complete resolution without treatment 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of Bell's palsy is 40 000 new cases each year with 8% to 12% recurrence rate. 13 Up to 70% of patients will have complete resolution without treatment. 14 Even though the underlying pathophysiology remains elusive, Bell's palsy is thought to result due to virus-mediated inflammation resulting in swelling of the CN VII and its compression at the geniculate ganglion.…”
mentioning
confidence: 99%